2016
DOI: 10.1016/j.neubiorev.2016.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Linking cognitive and visual perceptual decline in healthy aging: The information degradation hypothesis

Abstract: Several hypotheses attempt to explain the relation between cognitive and perceptual decline in aging (e.g., common-cause, sensory deprivation, cognitive load on perception, information degradation). Unfortunately, the majority of past studies examining this association have used correlational analyses, not allowing for these hypotheses to be tested sufficiently. This correlational issue is especially relevant for the information degradation hypothesis, which states that degraded perceptual signal inputs, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 80 publications
9
70
0
Order By: Relevance
“…With respect to faces, expertise develops through extensive experience in individuating faces from childhood to adulthood (Grill-Spector, Golarai, & Gabrieli, 2008). Our finding that the context congruency effect is robust in MA and OA despite reduced signal strength suggests that holistic processing might partly compensate for perceptual degradation in aging (for a discussion of perceptual degradation and compensatory mechanisms, see Bertone et al, 2007;Monge & Madden, 2016).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…With respect to faces, expertise develops through extensive experience in individuating faces from childhood to adulthood (Grill-Spector, Golarai, & Gabrieli, 2008). Our finding that the context congruency effect is robust in MA and OA despite reduced signal strength suggests that holistic processing might partly compensate for perceptual degradation in aging (for a discussion of perceptual degradation and compensatory mechanisms, see Bertone et al, 2007;Monge & Madden, 2016).…”
Section: Discussionmentioning
confidence: 87%
“…Loss of CS begins at 50 years of age, especially at high spatial frequencies (SF), where the loss might be as high as 30% relative to younger adults (e.g., Neargarder, Stone, Cronin-Golomb, & Oross, 2003;Owsley, Sekuler, & Boldt, 1981). Recent meta-analyses indicate that both VA and CS are linked to impaired cognition in aging, even in the absence of known disease (La Fleur & Salthouse, 2014;Monge & Madden, 2016). With respect to faces, several studies have reported an association between perceptual loss and cognitive performance (Lott et al, 2005;Norton et al, 2009).…”
Section: Perceptual Degradation (Hypothesis 1)mentioning
confidence: 99%
See 2 more Smart Citations
“…"Impoverishment" of cognitive capacities occurs during the aging process [6]. The information degradation hypothesis claims that perceptual degradation of signal inputs caused by neurobiological processes connected with aging cause errors in the processing of perceptual information finally leading to disruption of higher order cognitive processes [7]. Reduced capacity for discrimination or differentiation stimulus causes damage in a large number of aspects of cognitive function associated with aging.…”
Section: Ageing and Cognitionmentioning
confidence: 99%